PENGARUH LATIHAN LADDER SPEED RUN TERHADAP KECEPATAN LARI PADA TIM FUTSAL PUTRA SMP NEGERI 13 PEKANBARU - Rewa Ridozuta; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is the lack of running speed on the men's futsal team at SMP Negeri 13 Pekanbaru, because players are slow to run to open up space forward and when they are about to counterattack the players are also very slow to run to open space to the opponent's defense area so that the opposing player has returned defensive position so the opportuAnity to score a goal has been closed. The title studied in this study is "The Effect of Ladder Speed Run Training on Running Speed in the Men's Futsal Team of SMP Negeri 13 Pekanbaru". So that the future goal for players to be able to show even better performance during futsal training and matches. The form of this research is (one group pretest-posttest design) with the population of the men's futsal team at SMP Negeri 13 Pekanbaru. The data in this study were the entire population of 10 people. The instrument used in this research is to use the 30 Meter Run test, which aims to find out how much influence the player's speed has. To test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test of X data, it produces Lcount of 0.210 and L table of 0.285, meaning L count < L table. while the variable Y produces Lcount of 0.205 and L table of 0.285. This means Lcount < L Table. then the data is normally distributed. Thus it can be concluded that for the influence between the x variable and the y variable based on the t-test analysis, it produces tcount > t table, namely (9,138) > (1,796), then Ha is accepted, in other words there is a significant influence on the effect of ladder speed run training on running speed. on the men's futsal team of SMP Negeri 13 Pekanbaru.Key Words: Ladder Speed Run Exercise, Running Speed